2019
DOI: 10.1007/s42380-019-00010-0
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Cyber Bullying/Victimization Among Adolescents: Examining Their Psychosocial Profile Through Latent Profile Analysis

Abstract: Although increasingly more studies investigate the relationship of cyber and traditional bullying/victimization, it is unclear whether the phenomena are distinct. The purpose of this study was to investigate the roles that Greek Junior High school students engage in cyber and traditional bullying/victimization incidents, as well as the psychosocial and emotional profiles of the students that are classified into each participant role. Overall, 1097 Greek Junior High school students (mean age = 13.95, 51% girls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 103 publications
5
42
4
Order By: Relevance
“…We identified only two studies that used a person‐centered approach to identify subgroups with distinct patterns of in‐person and cyber forms of aggression and victimization (i.e., Antoniadou et al, 2019; Liu et al, 2021). Both studies focused on bullying, a severe form of aggression that involves repeated and intentional acts of aggression and a power imbalance between the perpetrator and victim (Olweus, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…We identified only two studies that used a person‐centered approach to identify subgroups with distinct patterns of in‐person and cyber forms of aggression and victimization (i.e., Antoniadou et al, 2019; Liu et al, 2021). Both studies focused on bullying, a severe form of aggression that involves repeated and intentional acts of aggression and a power imbalance between the perpetrator and victim (Olweus, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that cyberbullying should be studied from an ecological perspective. This statement is based on the nature of this problem, since cyberbullying has the potential to extend beyond victims, to bystanders not confined to the same class, grade, school, or country, emphasizing the importance of considering the influence of the environmental contexts of the adolescent [8,9]. This theory provides a useful framework for examining the interplay between environmental factors and adolescent cyberbullying.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the fluidity extends to the styles of intervention used by bystanders. This fluidity in roles tends to be more prominent in cyberbullying than traditional bullying (Antoniadou et al 2019), possibly because of the increased anonymity and obscured impact on victims in the online world.…”
Section: Discussionmentioning
confidence: 99%
“…Although bystanders play a role in traditional bullying, this study specifically examines bystander intervention in cyberbullying episodes, as cyberbullying has escalated due to increased accessibility to the Internet and smartphones (Cassidy et al 2013). Despite adolescents showing similar behaviour in cyber and traditional bullying roles, cyberbullying warrants specific study due to its unique context (Antoniadou et al 2019). Some authors have suggested an online disinhibition effect contributes to online aggression, whereby individuals are more likely to engage in aggressive behaviour due to the anonymity, large audience and obscured impacts on victims afforded by the online context (Dooley et al 2009;Kokkinos and Voulgaridou 2017;Kowalski et al 2014;Slonje and Smith, 2008).…”
mentioning
confidence: 99%